Soil branched Glycerol dialkyl glycerol tetraether (brGDGT) distributions, soil temperatures, soil properties, and air temperatures of the Eastern Canadian Arctic and Iceland,2023-2024 ... - Raberg, Jonathan; Crump, Sarah; De Wet, Greg; Harning, David; Miller, Gifford; Geirsdóttir, Áslaug; Sepúlveda, Julio (NSF Arctic Data Center, 2024)
This dataset consists of lipid biomarker (branched glycerol dialkyl glycerol tetraether (brGDGT)) data, soil properties (pH, electrical conductivity, and soil water content), soil temperature data, and air temperature data for surface soils collected from the Eastern Canadian Arctic (ECA) and Iceland. These data were supplemented with brGDGT, soil property, soil temperature, and air temperature data from previously published studies from Iceland (De Jonge et al., 2019), China (Wang et al., 2020; Wang and Liu, 2021), Colombia (Pérez-Angel et al., 2020), and Scandinavia (Halffman et al., 2022). We collected soil samples at 0-10 centimeter (cm) depth from the Eastern Canadian Arctic (ECA; n = 44) and Iceland (n = 24) in the summers of 2015-2019. For 27 soil sites in the ECA and all soil sites in Iceland, we deployed in situ soil temperature loggers (Thermochron DS1925L or DS1922L iButtons, Maxim Integrated Products) at 10 cm depth for 1 to 2 years (362 – 727 days). All loggers had a 1- to 3-hourly sampling ...